EFEK ANTI JAMUR AIR RENDAMAN DAUN KELOR (Moringa oleifera) TERHADAP PERTUMBUHAN JAMUR Trichophyton mentagrophytes SECARA IN VITRO - jirna inyoman (Meditory : The Journal of Medical Laboratory, 2017)
Abstract Background Moringa oleifera is a plant that all parts can be used for medicinal purposes. Roots, flowers, bark, stems, leaves and seeds of Moringa has antimicrobial properties. Compound content in leaves of moringa, such as tannin,steroid, alkaloid, saponins ,and flavonoids . ObjectiveThe purpose of this research was to know the different of Trichophyton mentagrophytes growth on various leaves of moringa (Moringa oleifera) concentration extract. Methods This research uses a true experimental with post test only kontrol group design. The antifungal activity test use diffusion disk method, these were divided into four test group with concentration 25%, 50%, 75%, 100% and two kontrol group were positive kontrol (ketokonazole 2%) and negatif kontrol (sterile distilled water). The result of this study showed that the average diameter of inhibition zone of concentration 25% until 100% is 0 mm. Statistic analysis was done by using Kolmogorof Smirnov test and Kruskal Wallis test. The test showed there was not a significant mean difference between group. All consentration haven’t an effect on Trichophyton mentagrophytes growth inhibition zone diameter. For next research with same topics using pure extract leaves of moringa was recommended. Keywords: Inhibition zone, Moringa oleifera, Trichophyton mentagrophytes.